Implementasi MBKM pada Program Studi Akuntansi di Perguruan Tinggi Indonesia - Mariska Nur Hanifah; Nurul Fauziyyah (Accounting Department UNUSIA, 2023)
One of the most important aspects of life is education. The achievement of educational goals and the effectiveness of the learning process is truly supported by the curriculum. The curriculum ought to be adapted to the needs and developments of the times. The Ministry of Education and Culture launched the MBKM curriculum with the aim of encouraging students to master various scientific fields and practical opportunities that are useful for entering the world of work. This study aims to examine the understanding and readiness of Accounting Study Program students in implementing MBKM and provide an overview of the process of implementing MBKM policies in Indonesian Universities. This research is a literature study that analyzes and examines previous research, books, and data from credible sources. The data analysis method used in this research is descriptive qualitative analysis. The results of the study show a positive understanding of students regarding the policies, functions, and benefits obtained (outcomes) in the implementation of “Merdeka Belajar Kampus Merdeka” (MBKM) in the Accounting Study Program. Nonetheless, the process of implementing the MBKM Program certainly did not run smoothly without obstacles. By identifying these obstacles it can be used as an evaluation tool to improve the implementation of the MBKM program in the future.